2015
DOI: 10.3906/kim-1501-80
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen reduction on a polypyrrole coated Pt electrode under high-pressure conditions: electrochemical impedance spectroscopy studies

Abstract: Abstract:The electrochemical impedance spectroscopy (EIS) responses of a polypyrrole (PPy)-coated platinum electrode were investigated during N 2 -reduction to ammonia in aqueous medium. Kinetic parameters such as film resistance, pore resistance, and double layer capacitance were analyzed as a function of applied potential and polymer film thickness.The relation between kinetic parameters was discussed by combining electrolysis results. It was found that the optimum film thickness of polypyrrole was 0.73 µ m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In the low-frequency region, the process is controlled by reactant diffusion to the reaction site contributing to the linear part (i.e., Warburg impedance). 36,37 The R ct for MoFe/Cc-PAA and MoFe electrode were 25 and 150 Ω, respectively. The relationship between reactant concentration and charge-transfer resistance is characterized by the equation…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the low-frequency region, the process is controlled by reactant diffusion to the reaction site contributing to the linear part (i.e., Warburg impedance). 36,37 The R ct for MoFe/Cc-PAA and MoFe electrode were 25 and 150 Ω, respectively. The relationship between reactant concentration and charge-transfer resistance is characterized by the equation…”
Section: Resultsmentioning
confidence: 99%
“…In the high-frequency region, the semicircle diameter is a measure of the charge-transfer resistance, which is affected by the electron transfer crossing the electrode surface. In the low-frequency region, the process is controlled by reactant diffusion to the reaction site contributing to the linear part (i.e., Warburg impedance). , The R ct for MoFe/Cc-PAA and MoFe electrode were 25 and 150 Ω, respectively. The relationship between reactant concentration and charge-transfer resistance is characterized by the equation where R is the ideal gas constant, T is the temperature, n is the number of electrons involved in the redox process, F is Faraday’s constant, K et is the potential-dependent charge transfer, [S] is the concentration of redox molecules, and A is the geometric surface area of the electrode in cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…One semicircle was observed in the Nyquist plots for the three electrode surface, indicates to the interfacial electron transfer resistance ( R ct ), which characterizes the kinetics of the HER process 53 . The obtained impedance spectra are fitted by the classical Randles equivalent circuit model based on the only one constant phase element (CPE) as presented in Figure 9, 11,54 where R e stands for the electrolyte resistance.…”
Section: Resultsmentioning
confidence: 99%
“…304 This mechanism was similar to the one the authors suggested for N 2 reduction in the aqueous solution. 235 N 2 electroreduction in 2-propanol 305 and ethylenediamine 306 was examined by Kim et al In the first case, 305 the electrolyte was a mixture of 2propanol and deionized water (9:1, v/v) with 10 mM H 2 SO 4 as a supporting electrolyte, and a porous nickel electrode was used as the cathode (Figure 39d). As shown in Figure 39e, a significantly higher ammonia formation rate and Faradaic efficiency were obtained in the mixed solvent compared to those in water.…”
Section: N 2 Electroreduction In Nonaqueous Solventsmentioning
confidence: 99%
“…The low activity of Pt catalysts toward N 2 reduction is partially due to the endothermic nature of the binding energy of N adatoms on Pt surfaces (Figure ); therefore N 2 molecules are hardly adsorbed on the catalyst surface. To solve this problem, Köleli and Kayan , used a Pt plate coated with a polypyrrole film as an electrode material for N 2 reduction in an aqueous solution containing 0.1 M Li 2 SO 4 and 0.03 M H + . A N 2 pressure of 6 MPa was used in order to improve the solubility of N 2 in the reaction medium.…”
Section: Electrocatalytic Reduction Of N2 To Ammonia At Low Temperatu...mentioning
confidence: 99%